NEUROLINGUISTIC PROGRAMMING (NLP) IN THE MANAGEMENT OF TEACHERS' MENTAL STATES - Khoshimova Diloromkhan Anvarovna (Journal Park Publishing, 2024)
Effective management of teacher morale is essential to create a positive and effective learning environment. Neuro-linguistic programming (NLP) offers a set of techniques and strategies that can be used to improve the mental well-being and performance of teachers. This article explores the use of NLP in teacher mental health management, focusing on its potential benefits, key techniques and implications for educational management. By using NLP techniques such as anchoring, reframing, and modeling, administrators can increase teacher motivation, confidence, and resilience, leading to improved classroom outcomes and overall job satisfaction. The article also discusses the ethical considerations and issues surrounding the application of NLP in an educational context.